Does the Digital Transformation of an Organization Improve the Quality of Internal Controls? - Qin, Ziru (Transactions on Economics, Business and Management Research, 2024)
To explore the relationship and path mechanism between enterprise digital transformation and enterprise internal control quality, this paper selects A-share listed companies in Shanghai and Shenzhen from 2012 to 2021 as the research samples, adopts the text mining method to construct the degree of enterprise digitization metrics, empirically analyses the impact of the degree of enterprise digital transformation on the quality of enterprise internal control, and explores the path mechanism between the two from the perspective of the five elements of internal control. The results show that enterprise digital transformation can improve the quality of internal control. The results found that enterprise digital transformation can improve the quality of internal control of enterprises; that is, the two are significantly positively correlated; from the perspective of the five elements of internal control, enterprise digital transformation mainly improves the quality of enterprise internal control by improving the efficiency and ability of enterprise risk assessment, practical control activities, and improving the efficiency of information and communication; further research found that the better the degree of enterprise digital transformation, the worse the effect of financing constraints, and the worse the quality of enterprise internal control. The worse the effect, the better the quality of enterprise internal control. Heterogeneity analysis found that the magnitude of the degree of enterprise digital transformation on the quality of enterprise internal control is more remarkable in cities with low agency costs, low levels of the regional digital economy, technology-intensive enterprises, and manufacturing enterprises. The above conclusions have particular reference value for scientifically promoting the digital transformation and development of China's small and medium-sized enterprises and effectively promoting improving internal control.